Thanatophoric Dysplasia: A Report of 2 Cases with Antenatal Misdiagnosis - Lamidi Audu; Amina Gambo; Tokan Silas Baduku; Bilkisu Farouk; Anisa Yahaya; Kefas Jacob (Case Reports in Pediatrics)
Thanatophoric dysplasia (TD) is a rare but uniformly lethal inherited disorder of the skeletal system resulting from defects in the fibroblast growth factor receptor-3 gene on the short arm of chromosome ##4. It is characterised by pronounced shortening of the tubular bones resulting in significant short stature, macrocephaly, a funnel-shaped chest, protuberant abdomen, redundant skin in the limbs, and typical facies among others. The two clinical types of TD are differentiated by typical cranial and tubular bone configurations. Antenatal diagnosis is usually made in the last trimester and corroborated at birth. We present 2 cases of TD seen at Barau Dikko Teaching Hospital (BDTH) between January and August 2021 to highlight the potential difficulty with antenatal diagnosis, its diagnostic features, and associated early postnatal fatality. The antenatal diagnosis was missed in both cases in spite of repeated 2nd and 3rd-trimester sonographic examinations. Both babies presented with remarkable micromelic short stature with the telephone-handle appearance of the femoral bones characteristic of type 1 TD, developed progressive respiratory distress at birth, and died within 36 hours of life despite respiratory support with Bubble CPAP. These cases are discussed along with a review of existing relevant literature.